Constructing Patient Stories: 'Dynamic' Case Notes and Clinical Encounters at Glasgow's Gartnavel Mental Hospital, 1921–32. Issue 1 (10th December 2015) - Morrison, Hazel
Abstract : This article contextualises the production of patient records at Glasgow's Gartnavel Mental Hospital between 1921 and 1932. Following his appointment as asylum superintendent in 1921, psychiatrist David Kennedy Henderson sought to introduce a so-called dynamic approach to mental health care. He did so, primarily, by encouraging patients to reveal their inner lives through their own language and own understanding of their illness. To this effect, Henderson implemented several techniques devised to gather as much information as possible about patients. He notably established routine 'staff meetings' in which a psychiatrist directed questions towards a patient while a stenographer recorded word-for-word the conversation that passed between the two parties. As a result, the records compiled at Gartnavel under Henderson's guidance offer a unique window into the various strategies deployed by patients, but also allow physicians and hospital staff to negotiate their place amidst these clinical encounters. In this paper, I analyse the production of patient narratives in these materials. The article begins with Henderson's articulation of his 'dynamic' psychotherapeutic method, before proceeding to an in-depth hermeneutic investigation into samples of Gartnavel's case notes and staff meeting transcripts. In the process, patient–psychiatrist relationships are revealed to be mutually dependent and interrelated subjects of historical enquiry rather than as distinct entities. This study highlights the multi-vocal nature of the construction of stories 'from below' and interrogates their subsequent appropriation by historians.